Effect of variety, dates of planting and spraying with Growmore in some quantitative characteristics of dry cowpea horns - Saeed, Rana Kareem; Al- Shammari, Aziz Mahde Abed; Almubarak, Nadir F. (Journal of agricultural, environmental and veterinary sciences, 2019)
The experiment was conducted in a special field in the area of Kanaan for the province of Diyala for the autumn agricultural season 2017 to study the effect of the date of cultivation and spraying paper in the form of the fertilizer of the vine in the growth and the yield of three varieties of cowpea. The study included three factors, the first three varieties of cowpea namely; Blackeye, Kafr Al- Sheikh and Ramshorn, and the second date of agriculture and included two dates; the first on 15/7/2017 and the second on 1/8/2017, The third factor is the spraying of the paper in the growmore fertilizer, which includes three levels: the first 50 mg l- 1 and the second 100 mg l- 1 and the third 150 mg l- 1 in addition to the comparison treatment (0 mg l- 1). Thus, the experiment contained twenty- four treatments, which are the combination of the above factors. The experiment was carried out in accordance with the system of splitting the splinters with the design of the complete random sections (RCBD) and with three replicates. The number of experimental units reached 72 units. The results were analyzed using the statistical program SAS, and the differences between the averages were measured using the TOKI test at a probability level of 0.05. The results were summarized as follows: Blackeye was superior in most traits, giving the highest values of 100 seed weight, seed weight, seed yield per plant, total seed yield, respectively, 34.12 g, 0.344 g, 242.10 g,- 1, 12.92 ha. While Kafr El- Sheikh was superior in the number of dry corns of cowpea, 66.21 pods, which exceeded the number of cultivated plants on the first date in all studied traits. This is a good indication that early agriculture in mid- July increases the yield and its components. As for the grow more product, the spray concentration was significantly higher than 100 mg/ L- 1 in the weight of 100 seeds, seed yield per plant, total seed yield, respectively 30.85 g, 289.89 g and 15.46 ha- 1, , While spraying the plants with the chromor product with both concentrations 100 and 150 mg L- 1 to their superiority significantly "in the characteristics of the number of corns and the rate of weight of a single seed.